The non-indigenous dung beetle (Onthophagus nuchicornis) can effectively reproduce using the dung of indigenous eastern North American mammals - Alexe Indigo; Katelyn Stokes; Olivia Burchell; Paul Manning (PeerJ)
Non-indigenous dung beetle (Coleoptera: Scarabaeoidea) species in North America are important contributors to ecosystem functions, particularly in pasture-based livestock systems. Despite the significant body of research surrounding non-indigenous (and often invasive) dung beetles in agricultural contexts, there has been minimal study concerning the impact that these species may have on indigenous dung beetle populations in natural environments. Here we examine the possible impact of the introduced dung beetle Onthophagus nuchicornis on indigenous dung beetle populations via use of indigenous mammal dung. Using a controlled laboratory experiment, we quantified how readily beetles could use dung from bobcat (Lynx rufus), red fox (Vulpes vulpes), moose (Alces alces), raccoon (Procyon lotor), and domestic sheep (Ovis aries). To determine the suitability of each dung type for reproduction, we measured offspring abundance and fitness. While the number of developed offspring was significantly different among treatments, offspring fitness did not vary significantly across dung types. Our results demonstrate the generalist feeding habits of the non-indigenous dung beetle O. nuchicornis can allow this species to use the dung of various wild animals indigenous to eastern North America.